Spiro donor–acceptor TADF emitters: naked TADF free from inhomogeneity caused by donor acceptor bridge bond disorder. Fast rISC and invariant photophysics in solid state hosts. Issue 4 (4th January 2022) - Franca, Larissa Gomes; Danos, Andrew; Monkman, Andrew
Abstract : The molecular photophysics of 10-phenyl-10 H, 10′ H -spiro[acridine-9, 9′-anthracen]-10′-one (ACRSA) are used as an ideal molecule to probe how external factors affect the TADF and rISC mechanisms. Abstract : We have studied the thermally activated delayed fluorescence (TADF) properties of the spiro-bridged donor–acceptor molecule, 10-phenyl-10 H, 10′ H -spiro[acridine-9, 9-anthracen]-10′-one, (ACRSA) in guest–host films and used it as a probe to explore the details of host effects on the TADF mechanism in typical OLED host materials. Linked by the rigid spiro C–C bond rather than a flexible C–N bond, we observe no inhomogeneous effects arising from distributions of donor–acceptor bridge dihedral angles. ACRSA displays no time dependent 'apparent' red shift of the prompt or delayed charge transfer (CT) emission. Moreover, using a range of different hosts, we show that the ground state dipole moment (dielectric value) of the host has very little effect on the ACRSA CT energy, i.e. there is no so-called 'solid state solvatochromism'. This leads to weak stabilisation of the CT state in all hosts, but has a very small singlet triplet gap and very fast and efficient monoexponential rISC rates in films (reaching nearly 10 7 s −1 in zeonex host). We observe no power law decaying DF tail because there is no dispersion of the dihedral angle between donor and acceptor units. The previously much lower reported rISC rates in ACRSA are instead reattributed to intermolecular excimer states. The intermolecular species give rise to additional slow TADF contributions and broaden the overall CT emission band at 10% ACRSA loading and in neat films. Harnessing the rapid and homogenous rISC displayed by isolated ACRSA molecules may unlock higher efficiencies and – crucially – extended operational lifetimes in future TADF OLEDs.